Design and Analysis of Shock and Random Vibration Isolation of Operating Hard Disk Drive in Harsh Environment. (2009) - Harmoko, Hendri; Yap, Fook Fah; Vahdati, Nader; Li, Chuan
Abstract : An effective vibration isolation system is important for hard disk drives (HDD) used in a harsh mechanical environment. This paper describes how to design, simulate, test and evaluate vibration isolation systems for operating HDD subjected to severe shock and random vibrations based on military specifications MIL-STD-810E. The well-defined evaluation criteria proposed in this paper can be used to effectively assess the performance of HDD vibration isolation system. Design concepts on how to achieve satisfactory shock and vibration isolation for HDD are described. The concepts are tested and further enhanced by the two design case studies presented here. It is shown that an effective vibration isolation system, that will allow a HDD to operate well when subjected to severe shock and random vibration, is feasible.